2019
DOI: 10.3390/a12070131
|View full text |Cite
|
Sign up to set email alerts
|

Aiding Dictionary Learning Through Multi-Parametric Sparse Representation

Abstract: The ℓ 1 relaxations of the sparse and cosparse representation problems which appear in the dictionary learning procedure are usually solved repeatedly (varying only the parameter vector), thus making them well-suited to a multi-parametric interpretation. The associated constrained optimization problems differ only through an affine term from one iteration to the next (i.e., the problem’s structure remains the same while only the current vector, which is to be (co)sparsely represented, changes). We expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Our previous work [10,11] has shown encouraging results when adapting DL classification for FDI in water networks. In this paper we propose new methods that tackle large distribution networks and lift data dimensionality limitations by employing online DL strategies.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Our previous work [10,11] has shown encouraging results when adapting DL classification for FDI in water networks. In this paper we propose new methods that tackle large distribution networks and lift data dimensionality limitations by employing online DL strategies.…”
Section: Introductionmentioning
confidence: 92%
“…Dictionary learning (DL) [7] is an active field in the signal processing community with multiple applications such as denoising, compression, super-resolution, and classification. Recent studies have also shown good results when dealing with anomaly detection in general [21,22,23], and particularly when applied to the FDI problem in water networks [10,11].…”
Section: Dictionary Learning and Classification Strategiesmentioning
confidence: 99%
See 3 more Smart Citations